The role of socialprotection.org in fostering knowledge exchange and capacity-building in social protection through a knowledge brokering perspective - Mariana Balboni; Marina Carvalho; Patricia Velloso; Roberta Brito (International Policy Centre for Inclusive Growth (IPC-IG), 2022)
This report aims to analyse the socialprotection.org online platform's capacity to deliver knowledge exchange and capacity-building services to the global social protection community through a knowledge brokering perspective.
Keywords: 330; knowledge brokering; socialprotection.org; decision-making